A comparative study on the cellular viability and debridement efficiency of antimicrobial‐based wound dressings. Issue 1 (27th October 2019) - Chen, Rui; Salisbury, Anne‐Marie; Percival, Steven L.
Abstract: A concentrated surfactant gel containing polyhexamethylene biguanide (CSG‐PHMB) (CSG: Plurogel) was evaluated for in vitro cell cytotoxicity using the direct contact, extraction, and cell insert assays, along with its ability to breakdown artificial wound eschar and slough, compared with other clinically available wound gels: a wound gel loaded with 0.13% benzalkonium chloride (BXG) and a highly viscous gel loaded with 0.1% polyhexamethylene biguanide (PXG). Following treatment with CSG‐PHMB, BXG, and PXG at day 1, the viability of L929 and HDFa cells sharply decreased to lower than 20% of the culture media control in the direct contact assay; however, cell viability of L929 was 128.65 ± 1.41%, 99.90 ± 2.84%*, and 64.08 ± 5.99%* respectively; HDFa was 84.58 ± 10.41%, 19.54 ± 3.06%**, and 96.28 ± 33.67%, respectively, in the extraction assay. In the cell insert model, cell viability of L929 cells were 95.25 ± 0.96%, 47.49 ± 5.37%**, and 48.63 ± 7.00%**, respectively; HDFa cell viability were 92.80 ± 1.29%, 38.86 ± 4.28%**, and 49.90 ± 2.55%** (*: P < .01; ** P < .001 compared with CSG‐PHMB; cell viability of culture medium without treatment at day 1 was 100%). The cell extraction model on day 1 indicated that CSG‐PHMB had higher viability of L929 cells compared with BXG. In addition, the cellular viability results indicated that CSG‐PHMB gel exhibited lower cytotoxicity when compared with BXG and PXG in the cell insert model assay. Within the in vitro debridement model, CSG‐PHMB exhibited an ability to potentially increase the loosening of the collagen matrix. The reason for this may be because of the concentrated surfactant found within the CSG‐PHMB, which has the ability to lower the surface tension, aiding in the movements of fragments and debris in the fluorescent artificial wound eschar model (fAWE).